Identification of human herpes virus 1 encoded microRNAs in biopsy samples of lower esophageal sphincter muscle during peroral endoscopic myotomy for esophageal achalasia. Issue 1 (3rd October 2019) - Ikebuchi, Yuichiro; Kanda, Tsutomu; Ikeda, Haruo; Yoshida, Akira; Sakaguchi, Takuki; Urabe, Shigetoshi; Minami, Hitomi; Nakao, Kazuhiko; Kuwamoto, Satoshi; Inoue, Haruhiro; Isomoto, Hajime
Abstract : Esophageal achalasia is a rare chronic debilitating disorder characterized by incomplete lower esophageal sphincter (LES) relaxation and abnormal peristalsis as a result of myenteric plexus degeneration. Although complex interactions among immunity, viruses and inheritance have been proposed, its causes remain unknown. MicroRNAs (miRs) play crucial roles in the regulation of gene expression during pathophysiological processes. Certain viruses such as herpes simplex virus (HSV) encode miRs derived from their own genomes. To determine the underlying relationship of miRNAs to achalasia, we analyzed the expression profile of miRNAs using biopsy samples obtained from LES muscle during peroral endoscopic myotomy. Peroral LES muscle biopsy sampling was uneventfully carried out in our case series of achalasia. Control biopsy tissues were also obtained from LES muscle of patients without symptoms relating to abnormal esophageal motility whose esophagogastric junction was surgically excised. RNA was extracted from biopsy specimens and analyzed using a microarray. Differentially expressed miRNAs in achalasia patients compared to controls were identified and analyzed using reverse transcription quantitative polymerase chain reaction. HSV‐1‐derived hsv1‐miR‐H1 and ‐H18 was significantly overexpressed in achalasia cohorts compared to controls. Correlations between the expression levels of viral miR and the patients' clinical characteristics including achalasia morphological type, dilatation grading, and disease duration were not identified. Further studies with a larger sample size are needed to replicate the current heuristic identification of neurotropic viral miRs and unravel their functional significance in order to provide new insight linking neurodegenerative etiology in achalasia.